Comparison of manganese laurate, manganese palmitate and manganese stearate on accelerating degradation of HDPE during natural weathering - Maryudi, M.; Dewayanto, Nugroho; Beg, M. D. H.; R. M., Yunus (Penerbit Universiti Teknologi Malaysia, 2017)
High density polyethylene (HDPE) degradation has been studied. In this study, HDPE was incorporated with manganese laurate, manganese palmitate and manganese stearate as pro-oxidant additives. Preparation of samples were conducted by adding the HDPE resin with pro-oxidant additives in the range of 0-1.0 wt %. A twin screw extruder was employed prior to the injection molding technique. Samples were subjected to natural weathering for the maximum duration of 24 weeks. Assessments on the change of the properties of samples after natural weathering treatment were conducted by FTIR analysis, tensile testing and average molecular weight analysis. In term of their capabilities to accelerate degradation of HDPE, manganese stearate exhibited more influence than manganese laurate and manganese palmitate. The carbonyl group’s peak arises as a result of oxidation during the treatment as revealed by FTIR traces. Samples with pro-oxidant additives shows a loss of their strain at break. The amount of pro-oxidant additives increases the degradation of samples.